Cryptosporidium hominis Phylogenomic Analysis Reveals Separate Lineages With Continental Segregation - Cabarcas, Felipe; Galvan-Diaz, Ana Luz; Arias-Agudelo, Laura M.; García-Montoya, Gisela María; Daza, Juan M.; Alzate, Juan F. (Frontiers in Genetics, 2021)
Cryptosporidium is a leading cause of waterborne outbreaks globally, and Cryptosporidium hominis and C. parvum are the principal cause of human cryptosporidiosis on the planet. Thanks to the advances in Next-Generation Sequencing (NGS) sequencing and bioinformatic software development, more than 100 genomes have been generated in the last decade using a metagenomic-like strategy. This procedure involves the parasite oocyst enrichment from stool samples of infected individuals, NGS sequencing, metagenomic assembly, parasite genome computational filtering, and comparative genomic analysis. Following this approach, genomes of infected individuals of all continents have been generated, although with striking different quality results. In this study, we performed a thorough comparison, in terms of assembly quality and purity, of 100+ de novo assembled genomes of C. hominis. Remarkably, after quality genome filtering, a comprehensive phylogenomic analysis allowed us to discover that C. hominis encompasses two lineages with continental segregation. These lineages were named based on the observed continental distribution bias as C. hominis Euro-American (EA) and the C. hominis Afro-Asian (AA) lineages.